THE INFLUENCE OF SERVICE QUALITY, TRUST, AND FACILITIES ON THE DECISION TO CHOOSE SP HOTEL BATAM - Mohamad Aras; Indra Nara Persada; Septa Diana Nabella (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
This study aims to determine the effect of service quality, trust, and facilities on the decision to choose SP Hotel Batam. The type of research in this study is causality research, namely research that is structured to examine the possibility of a causal relationship between variables with a survey method. The data analysis method uses quantitative analysis. The location of this research is SP Hotel Batuaji, Batam City, Riau Islands, Indonesia.  The population of this study were local hotel guests staying at SP Hotel Batam in 2022, totaling 520 people and a sample of 84 respondents. The instruments used in this study were observation, interview, and questionnaire. The data analysis technique uses validity and reliability tests before testing the hypothesis, first testing for deviations from classical assumptions will be carried out. In classical assumptions there are several tests that must be carried out, namely Normality Test, Multicollinearity Test and Heterosdasticity Test using SPSS version 23. Then do a hypothesis test using the t test, F test, and analysis of the coefficient of determination (R2). Partial research results Service quality has a positive and significant effect on the decision to choose SP Hotel Batam, where the t count for service quality is 7.505> 1.664 t table and significance 0.000 <0.05. Trust has a positive and significant effect on the decision to choose SP Hotel Batam, where the t count for trust is 2.195> 1.664 t table and significance 0.031 <0.05. Facilities have a positive and significant effect on the decision to choose SP Hotel Batam, where the t count for facilities is 3.985> 1.664 t table and significance 0.000 <0.05. simultaneously Service quality, trust and facilities simultaneously have a positive and significant effect on the decision to choose SP Hotel Batam¸ with F count of 75.252> 2.72 F count with a significant level of 0.000. because the probability (0.000) is smaller than 0.05, thus the formulation of the problem and the fourth hypothesis can be accepted, it simultaneously affects the selection decision.